Impact of exogenous antithrombin on low molecular weight heparin anti‐Xa activity assays in a pediatric and young adult leukemia and lymphoma cohort with variable antithrombin levels. Issue 11 (25th August 2020) - Schaefer, Beverly; Hausfeld, Adriane; Martin, Matthew; Steele, Paul; Martin, Jan; Reher, Sandra R.; Lane, Adam; Luchtman‐Jones, Lori
Abstract: Background: Low molecular weight heparin (LMWH) remains the most commonly prescribed pediatric anticoagulant. There is debate whether LMWH anti‐Xa assays with or without exogenous antithrombin (AT) best reflect anticoagulation effect, and how much discrepancy exists between assay types. Objectives: We assessed the effect of variable AT activity on LMWH anti‐Xa levels in plasma samples from anticoagulated pediatric and young adult acute lymphoblastic leukemia and lymphoma (ALL/L) patients, using two instruments and their commercial kits with and without exogenous AT (ie, four platforms). Methods: We analyzed LMWH anti‐Xa levels on 60 plasma samples with known AT activity from 12 enoxaparin‐treated ALL/L patients, using four commercial kits from Siemens and Stago containing AT or not, on Siemens BCS and Stago STA R Max, respectively. Results: Of 236/240 samples with interpretable results, mean AT activity was 80% (46‐138%). Correlation was acceptable for published kit ranges of LMWH anti‐Xa levels when comparing kits containing AT ( r  = 0.82, P  < .0001), or not ( r  = 0.93, P  < .0001), and within a manufacturer (Berichrom to Innovance, r  = 0.92, P  < .0001; Stachrom to STA‐Liquid Anti‐Xa r  = 0.98, P  < .0001). LMWH anti‐Xa levels were lower in platforms without added AT ( P  < .0001). For Stago kits, this effect increased when AT < 70% ( P  = .001, n = 19, mean 56%). Assay variability, measured as mean percent difference, was less pronounced with Stago kits (14.7%, n = 49) than Siemens (41.9%, n = 50). Conclusions: Although LMWH levels from anti‐Xa assays with added AT trend higher than in those without, correlation was fairly good between platforms in pediatric ALL/L plasmas, even when AT activity was <70%.